Air pollution and skin disorders - Wendy Roberts, MD, FAAD (Wolters Kluwer, 2021)
Air pollution is being shown to play an increasing causation role in our most common skin diseases. Acne, hyperpigmentation, atopic dermatitis, and psoriasis have been shown to be influenced by air pollution. It is important for pollution to be added as a risk factor for these skin disorders, and thus we must discuss mitigating its negative affects with patients. Air pollution is the contamination of outdoor (ambient) and indoor (household) environments by any chemical, physical, or biological agent that modifies the natural characteristics of the atmosphere. Nearly all (90%) of the world's population experience daily pollution. In 2019, air pollution was considered by the World Health Organization to be the biggest environmental health risk to humans, responsible for killing more than 7 million people prematurely every year. Preliminary studies link air pollution to COVID-19 deaths, as there were high death tolls in some of the most globally polluted areas. Air pollution affects many organ systems such as cardiovascular, pulmonary, central nervous, reproductive, and integumentary systems. In this study, we detail the current evidence linking specific skin and health disorders to air pollution.